ANALISIS KESIAPAN PENERAPAN REKAM MEDIS ELEKTRONIK (RME)DI RSUP DR. M. DJAMIL PADANG - Vesri Yoga; Bestari Jaka; Mendhel Yanti (Universitas Baiturrahmah, 2021)
Introduction: The use of Electronic Medical Records (EMR) can provide great benefits for health services such as basic service facilities and referrals (hospitals). Currently, RSUP dr. M. Djamil plans to implement services with electronic medical records for services efficiency and improve the quality of services provided for patients, and ensure patient safety. Therefore, it is necessary to conduct a readiness assessment before implementing EMR. This will help identify processes and priority scales, as well as help establish operational functions to support the optimization of EMR implementation. Research objectives to analyze the readiness of implementing electronic medical records at RSUP dr. M. Djamil Padang. Methods: The research design used in this research is a case study with a qualitative approach. The research was conducted at the RSUP dr. M. Djamil Padang. The research activity was started from August to October 2020. The informants in this study were selected based on the purposive sampling method. Results: This study shows that organizational culture readiness is quite ready. Knowledge related to the application of EMR has been disseminated to all medical staff and medical support and experience in implementing EMR in the Emergency Room, which was currently running, there were still obstacles, still use manual printouts at the end. Regarding the readiness of governance and leadership, RSUP dr. M. Djamil Padang has a clear vision in implementing EMR. The average informant is optimistic that the change in the manual to electronic medical record system (EMR) can be successfully implemented in RSUP dr. M. Djamil Padang because the EMR can provide benefits for the hospital. The readiness of human resources for medical support is still in a gradual process. For infrastructure readiness, hardware and software can be implemented at RSUP dr. M. Djamil Padang in implementing EMR, although there were still some obstacles, the hospital is optimistic that the implementation of this EMR will run well. Conclusion: EMR implementation readiness still needs to be improved, such as organizational culture readiness, governance and leadership readiness, Human Resources (HR) readiness, and infrastructure readiness.